2023
DOI: 10.3847/2041-8213/acaf5e
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Gamma-Ray Burst Models from GRB 221009A: GeV Gamma Rays versus High-energy Neutrinos

Abstract: Gamma-ray bursts (GRBs) are generally believed to be efficient particle accelerators. In the presence of energetic protons in a GRB jet, interactions between these protons and the intense radiation field of the GRB are supposed to induce an electromagnetic cascade. Electrons/positrons generated in the cascade will produce an additional spectrum of a robust feature, which is in the form of a power-law distribution up to a GeV regime with an index of ≲2. We suggest that measurements of the Fermi Large Area Teles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Protons or heavier nuclei entrained in the outflow can also be accelerated by these mechanisms and produce high-energy TeV-PeV neutrinos on collisions with background photons (Waxman & Bahcall 1997;Becker et al 2006;Murase & Nagataki 2006;Hummer et al 2012;Bustamante et al 2015;Biehl et al 2018;Pitik et al 2021;Ai & Gao 2023;Liu et al 2023;Rudolph et al 2023). Prior to the prompt emission, internal collisions of protons and neutrons below the photosphere have been considered as a source of GeV neutrino emission (Bahcall & Meszaros 2000;Bartos et al 2013;Murase et al 2013Murase et al , 2022.…”
Section: Neutrinos From Gamma-ray Burstsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protons or heavier nuclei entrained in the outflow can also be accelerated by these mechanisms and produce high-energy TeV-PeV neutrinos on collisions with background photons (Waxman & Bahcall 1997;Becker et al 2006;Murase & Nagataki 2006;Hummer et al 2012;Bustamante et al 2015;Biehl et al 2018;Pitik et al 2021;Ai & Gao 2023;Liu et al 2023;Rudolph et al 2023). Prior to the prompt emission, internal collisions of protons and neutrons below the photosphere have been considered as a source of GeV neutrino emission (Bahcall & Meszaros 2000;Bartos et al 2013;Murase et al 2013Murase et al , 2022.…”
Section: Neutrinos From Gamma-ray Burstsmentioning
confidence: 99%
“…Murase et al (2022),Liu et al (2023), andRudolph et al (2023). Previous IceCube searches for the joint neutrino emission of GRBs showed that high-energy neutrino emission during the prompt phase (or during 10 4 s) of GRBs is limited to 1% (or 24%) of the high-energy diffuse neutrino flux observed byIceCube (Abbasi et al 2022a).Future upgrades and proposed extensions of IceCube could provide a crucial step toward neutrino detection from GRBs.…”
mentioning
confidence: 98%
“…We consider the two extreme values 0.62 and 1.25, which correspond to the minimum and maximum best-fit values of the prompt GRB intrinsic spectral index given by the assumed background bracketing (see Section 4.3). For Γ j = 700 (Liu et al 2023), θ j = 1.5°, and q q = v j 2 3 , we obtain 16% and 36%, respectively. This range is consistent with the measured upper limits.…”
Section: Discussionmentioning
confidence: 77%
“…Note. During completion of this work, Liu et al (2023) appeared. In contrast to their paper, we self-consistently model the photon spectra and account for several emission regions along the jet.…”
Section: Discussionmentioning
confidence: 99%